POWER ASSISTED TRANSORAL ENDOSCOPIC VS CONVENTIONAL ADENOIDECTOMY- A COMPARISON - DR.S.SUNDARA PANDIAN,; DR. SHOBA T., (International Journal of Pharma and Bio Sciences, 2014)
To evaluate and compare the efficiency of Power Assisted Transoral Endoscopic (PATE) with the Conventional Adenoidectomy (CA). A prospective study involving 50 patients in which 25 underwent PATE and 25 underwent CA.The residual adenoid tissue at 3 months and 6 months after surgery were compared.Residual adenoid was less in PATE than CA, operating time was more in PATE than CA.There was no difference in operative blood loss and complications between the two methods.PATE is a safe and efficient way to do an adenoidectomy.